IMPLEMENTASI VIDEO ANIMASI BERBASIS APLIKASI CANVA UNTUK MENINGKATKAN MINAT BELAJAR SISWA MATA PELAJARAN FIKIH MTsN 7 ACEH UTARA - ‘Asyrina, Muharmi (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2025)
The development of information and communication technologies encourages learning innovations that are adaptive to the needs of the digital generation. One potential medium is animated videos, which are able to present material visually, interactively and contextually. This research was motivated by students' low interest in learning in the Jurisprudence class IX MTsN 7 North Aceh subject due to the dominance of conventional monotonous methods. The aim of the research is to analyze the implementation and influence of the use of Canva application-based animated videos on increasing students' interest in learning in Qurban and Aqiqah materials. The research used a descriptive qualitative approach with data collection techniques in the form of observations, semi-structured interviews and documentation. Data analysis is carried out through reduction, presentation and verification stages. Results showed that the application of Canva animated videos significantly contributed to the improvement of attention, understanding, and participation of students, while supporting the pedagogical effectiveness of teachers. Despite technical constraints, this medium has proved to be relevant and effective in strengthening learning motivation.